2015
DOI: 10.1111/jphp.12310
|View full text |Cite
|
Sign up to set email alerts
|

A review on phytochemistry, pharmacology and toxicology studies of Aconitum

Abstract: Objectives A number of species belonging to herbal genus Aconitum are wellknown and popular for their medicinal benefits in Indian, Vietnamese, Korean, Japanese, Tibetan and Chinese systems of medicine. It is a valuable drug as well as an unpredictable toxic material. It is therefore imperative to understand and control the toxic potential of herbs from this genus. In this review, the ethnomedicinal, phytochemistry, pharmacology, structure activity relationship and toxicology studies of Aconitum were presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(147 citation statements)
references
References 139 publications
(285 reference statements)
2
144
0
1
Order By: Relevance
“…Hai-Ha Ni in the USA, BuTao Chang (1942-2012) in Taiwan, Chin-An Zheng (1824Zheng ( -1911 in China, and other prominent TCM physicians introduced different therapeutic regimens containing Fuzi. Aconitum was prescribed for its cardiotonic, antiarrhythmic, analgesic, anti-epileptiform, anticancer and antimicrobial activities [3]. In order to maximize the clinical effects, some followers of Chin-An Zheng recommended the use of raw or processed Fuzi in a dose as high as 60-120 g, which was 4-8 times the dosage recommended by previous practitioners.…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Hai-Ha Ni in the USA, BuTao Chang (1942-2012) in Taiwan, Chin-An Zheng (1824Zheng ( -1911 in China, and other prominent TCM physicians introduced different therapeutic regimens containing Fuzi. Aconitum was prescribed for its cardiotonic, antiarrhythmic, analgesic, anti-epileptiform, anticancer and antimicrobial activities [3]. In order to maximize the clinical effects, some followers of Chin-An Zheng recommended the use of raw or processed Fuzi in a dose as high as 60-120 g, which was 4-8 times the dosage recommended by previous practitioners.…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
“…Aconitum was first introduced in Shennong Ben Cao Jing, which is the earliest Chinese herbs book and might be written around the era of Qin to Western Han Dynasties (221-200 BC) [24,25]. Aconitum preparations, including Fuzi (aconiti radix lateralis praeparata), Wutou (chuan wu, aconiti radix praeparata), and Caowu (A. kusnezoffii), have been recommended for cold limbs, painful knees, walking difficulties, chronic wounds, poor circulation, spasms, and different tumors [3]. The applications of Aconitum were advocated in Shang Han Lun, which was written by Zhang Zhongjing, one of the most respected TCM physicians in history.…”
Section: Traditional Chinese Medicinementioning
confidence: 99%
“…that have been isolated from Chinese herbal medicine, the tubers and roots of Aconitum (Ranunculaceae) and Aconitum napellus are particularly rich in β-3, 4-dihydroxyphenethyl β-glucopyranoside [74].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Moreover, recent review showed that certain alkaloids are medicinally applied as local anesthetic [70], stimulants -(caffeine, nicotine, threobromine, methylated derivatives of xanthine, methylated uric acids such as theacrine, methylliberine and libertine [7]), psychedelics, analgesics -(morphine [72,73], codeine [41], N-methyl-N-deethylaconitine [74]), bactericidal-(piperidine [75], harmandiamines A-C [76]), anti-cancer drugs -(camptothecin, vinblastine, vincristine [7,77]), anti-hypertensive agents -(serpentine [78][79][80][81]), cholinomimerics -(aceclidine [41]), spasmolysis agents - [82], vasodilators -(rutaecarpine [83]), anti-arrhythmia, anti-asthma [41], anti-malarials (quinine and artemisinin [7]) etc.…”
Section: Isolation Identification and Characterization Of Bioactive mentioning
confidence: 99%
“…Development of ventricular tachyarrhythmia and heart arrest will result in death. No specific therapy exists for Aconitum poisoning, so it should not be used in pregnancy 10,15 Acorus calamus L., Bach: In view of toxic property of betaasaron associated with Calamus, it should be avoided in pregnancy and lactation. It has emmenagogue and genotoxic activity 11,16 Adhatoda zeylanica, Adusa / Vasaka: Abortifacient and hence should not be used during pregnancy, Uterotonic activity, Root bark powder decoction 50-100 ml.…”
Section: Adverse Effect and Safety Of Traditional Drugs In Pregnant Amentioning
confidence: 99%